Prognostic Significance of Hyponatremia Leukocytosis, Hypomagnesemia, and Fever after Aneurysmal Subarachnoid Hemorrhage - Vrsajkov Vladimir; Jovanović Gordana; Galešev Marija; Uvelin Arsen; Glišić Dunja; Pantić-Vrsajkov Jelena (Indian Journal of Neurosurgery)
Abstract